IN PROGRESSING POPULATION ENTREPRENEURSHIP AND ENTREPRENEURIAL CULTURE - A REPLACEMENT OF ECONOMIC BEHAVIOR - Djuraev Lukmon Narzullaevich (Scholar Express Journals, 2024)
In this article, the population depends on the economic culture in raising the business mindset, and the economic behavior of the population as a whole system is effectively covered. It has been scientifically analyzed that economic culture, production culture is a whole social system, and its use is effective only if it is implemented in a complex way.
Keywords: Population; research; competitive